2016
DOI: 10.1016/j.reprotox.2016.03.042
|View full text |Cite
|
Sign up to set email alerts
|

Mono-2-ethylhexyl phthalate disrupts neurulation and modifies the embryonic redox environment and gene expression

Abstract: Mono-2-ethylhexl phthalate (MEHP) is the primary metabolite of di-2-ethylhexyl phthalate (DEHP), a ubiquitous contaminant in plastics. This study sought to determine how structural defects caused by MEHP in mouse whole embryo culture were related to temporal and spatial patterns of redox state and gene expression. MEHP reduced morphology scores along with increased incidence of neural tube defects. Glutathione (GSH) and cysteine (Cys) concentrations fluctuated spatially and temporally in embryo (EMB) and visce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 82 publications
(104 reference statements)
1
25
0
Order By: Relevance
“…Previous work from our laboratory has demonstrated that exposure to MEHP during early organogenesis may result in stunted growth and delayed or halted neurulation [30]. In this study, nutritional deficiencies were observed as changes in nutrient and cofactor uptake and availability after exposure to MEHP, suggesting that embryonic exposures to toxicants may reduce essential nutrient supplies and produce a canonical stunting of growth.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…Previous work from our laboratory has demonstrated that exposure to MEHP during early organogenesis may result in stunted growth and delayed or halted neurulation [30]. In this study, nutritional deficiencies were observed as changes in nutrient and cofactor uptake and availability after exposure to MEHP, suggesting that embryonic exposures to toxicants may reduce essential nutrient supplies and produce a canonical stunting of growth.…”
Section: Discussionmentioning
confidence: 56%
“…Mouse embryo culture (mWEC) was performed following the conditions outlined in [31], and described in [30]. Briefly, female CD-1 mice were time-mated and obtained from Charles River (Portage, MI).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations